Beyond Groceries: Financial Confidence and the Gender Gap in Inflation Expectations - Lovisa Reiche (CESifo GmbH, 2024)
The gender gap in inflation expectations, women reporting systematically higher expectations in consumer surveys, has been attributed to traditional gender norms, and thus women's greater exposure to volatile food prices. This overlooks a crucial factor: financial answer confidence. Using data from German households, I show that the "grocery shopping" effect occurs only among those with low answer confidence, while there is no gap among those with high answer confidence. The interaction of financial answer confidence and the shopping experience can be explained through the lens of a simple Bayesian learning framework, where noisy signals only increase mean expectations when priors are imprecise.
Keywords: E31; E71; G53; 330; consumer inflation expectations; gender; financial literacy